A new method for inspection and detection of typical defects of protective facilities in existing railways and its application - Li, Jian; Gao, Xu; Lv, Huayong; Guo, Hongze; Wang, Zonghao; Cheng, Zhanbo (Frontiers in Earth Science, 2024)
Due to the frequent occurrence of defects of slope protection facilities on existing lines causing the potential major geological hazards (e.g., landslides), it is necessary to promote the inspection and detection efficiency of various defects of slope protection facilities for carrying out early warning and evaluation, as well as, putting forward relevant control measures for slope disasters. Based on the case studies of hundreds of protective facilities on the existing railway line, the typical defect types, characteristics and specific causes of retaining wall, slope protection, anti-slide pile and anchorage engineering structure are firstly determined. Subsequently, a new comprehensive method combining unmanned air vehicle (UAV) and intelligent detection of portable radar (IDPR) are proposed. Among of them, UAV can effective and efficient identify the defect situations of slope protection facilities, and the water accumulation and cracks of retaining wall through performing a periodic inspection of the surrounding environment of protective facilities. In addition, IDPR can detect the filling situations behind the protective facilities to prevent the collapse danger. Through comparison with the drilling core results of tested areas, it is found that the detection results of the IDPR are more reliable and accurate, which is worthy of popularization and application in the field.